Mobile Tracking Attendance of Branch Manager PT. Stars International - Suhairi; R Dimas Adityo; Mas Nurul Hamidah (JEECS (Journal of Electrical Engineering and Computer Sciences), 2020)
Nowadays technological developments in daily life are increasingly developing. In the world of work, information technology is needed, especially in absenteeism this is still mostly done manually and fraud often occurs. At PT. Stars International in doing absenteeism the presence of managers is still using the manual method so the process absenteeism cannot be monitored directly. Likewise in the making Report managers have also been using the same method and very consuming time. Then made the system Mobile Attendance Tracking Branch Manager's goal is to avoid cheating in attendance at PT.Stars International. After doing Mobile Manager Attendance Tracking testing company admin can be directly monitor managers during visits based on the distance between store locations and manager positions and attendance process at PT. Stars International, a comparison between using methods Euclidean Distance with Google Maps has a percentage error of about 16.4% after it is done testing with 10 different sample data with Rungkut Stars Stars as points reference.